PERKAWINAN BEDA AGAMA MENURUT PERSPEKTIF FUQAHA - Luqman (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
This study aims to reveal how the fuqaha's perception of interfaith marriage is. Fiqh experts in Islam are the most authoritative parties to answer various religious issues, because they are the ones who best understand the arguments of the texts of the Koran and hadith. This research will be answered through three main discussions, marriage of Muslim men or women to polytheistic men or women, marriage of Muslim men to women of the Ahlul Kitab, and marriage of Muslim women to non-Muslim men in general. This type of research uses library research, explores fiqh literature and authoritative interpretations from various schools of thought, then analyzed and studied through in-depth interpretations and finally conclusions are drawn. The results of this study conclude that interfaith marriage according to the fuqaha perspective is divided into three classifications; First, the marriage of a Muslim man or woman with a polytheist is explicitly forbidden in the Qur'an and hadith. The two marriages of a Muslim man with a woman from the people of the book, according to the law of origin, are permissible, as the first specialization. Then it is considered makruh because of the demographic conditions of Muslims. The third is the marriage of a Muslim woman to non-Muslims in general, polytheists, people of the book, Zoroastrians and others. The law is forbidden based on the text of the verses of the Koran, hadith, ijma' and qiyas.